Acute Kidney Injury and Bloody Diarrhea in Falciparum Malaria - Widdy Winarta; Gevanski Maturbongs (Cermin Dunia Kedokteran, 2018)
Malaria remains one of the deadliest infectious disease worldwide. In adults, one of the commonest complication of falciparum malaria is acute kidney injury. Bloody diarrhea is rarely documented. This is a case report of a 24 year-old male with falciparum malaria presenting to the emergency department with fever, vomiting, bloody diarrhea, and decreased urine output. The patient was given rehydration therapy and antiemetics before administration of artesunate and primaquine. After three days, the patient had recovered. Acute kidney injury was primarily caused by dehydration, which explained the rapid recovery of the serum marker after proper fluid resuscitation. Exclusion of other potential pathogens must be done in a case of falciparum malaria with bloody diarrhea.Malaria masih merupakan salah satu penyakit infeksius paling mematikan di dunia. Pada dewasa, komplikasi paling sering malaria falsiparum adalah gagalginjal akut. Diare berdarah jarang dilaporkan. Laporan ini kasus pasien laki-laki usia 24 tahun dengan malaria falsiparum dengan keluhan demam, muntah, diare berdarah, dan penurunan jumlah urin. Pada pasien dilakukan rehidrasi dan pemberian antiemetik sebelum diberi artesunat dan primakuin. Setelah tiga hari pengobatan, pasien kembali normal. Gagal ginjal akut disebabkan terutama oleh dehidrasi, yang menjelaskan cepatnya pemulihan kadar ureum dan kreatinin setelah resusitasi cairan yang tepat. Eksklusi penyebab pathogen potensial harus dilakukan pada kasus diare berdarah pada malaria falsiparum.